2019
DOI: 10.1542/peds.2018-1828
|View full text |Cite
|
Sign up to set email alerts
|

Initial Oxygen Use for Preterm Newborn Resuscitation: A Systematic Review With Meta-analysis

Abstract: The International Liaison Committee on Resuscitation prioritized to review the initial fraction of inspired oxygen (Fio 2) during the resuscitation of preterm newborns. OBJECTIVES: This systematic review and meta-analysis provides the scientific summary of initial Fio 2 in preterm newborns (<35 weeks' gestation) who receive respiratory support at birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 42 publications
0
78
0
1
Order By: Relevance
“…Given the low-grade quality of the studies due to risk of bias and imprecision there is still uncertainty as to whether the use of higher or lower initial FiO 2 affects mortality, major morbidities or long-term neurodevelopmental disability in preterm infants (35). Welsford et al performed a systematic review and meta-analysis gathering evidence comparing different levels of FiO 2 employed to initiate resuscitation of preterm infants who require positive pressure ventilation in the DR (36). A total of 5697 preterm infants <35 weeks' gestation participating in 10 randomized/quasi randomized controlled and 4 retrospective observational cohort studies were analyzed.…”
Section: Comprehensive Updated Reviews and Meta-analysesmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the low-grade quality of the studies due to risk of bias and imprecision there is still uncertainty as to whether the use of higher or lower initial FiO 2 affects mortality, major morbidities or long-term neurodevelopmental disability in preterm infants (35). Welsford et al performed a systematic review and meta-analysis gathering evidence comparing different levels of FiO 2 employed to initiate resuscitation of preterm infants who require positive pressure ventilation in the DR (36). A total of 5697 preterm infants <35 weeks' gestation participating in 10 randomized/quasi randomized controlled and 4 retrospective observational cohort studies were analyzed.…”
Section: Comprehensive Updated Reviews and Meta-analysesmentioning
confidence: 99%
“…Higher initial FiO 2 was defined as ≥0.5, and lower <0.5. Results concluded that starting with either initial FiO 2 did not influence the primary outcome of short-term mortality [risk ratio (RR) 0.83, 95% confidence interval (CI) 0.50-1.37], long-term mortality, neurodevelopmental impairment, or other morbidities (36). It should be underscored that the meta-analysis included studies from 1980 to 2018 encompassing a wide range of different guidelines, study designs, devices, and gestational ages.…”
Section: Comprehensive Updated Reviews and Meta-analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Maintain a warm delivery room of about 26 Celsius. Fio 2 if required is given at 30% in <28 weeks of gestation, for 28-31weeks gestation Fio 2 of 21-30% is used and in >32 weeks gestational age 21% Fio 2 is used [12,13]. The aim is to achieve an SpO 2 of 80% or more by the end of 5 minutes in order to reduce mortality and intracranial hemorrhage.…”
Section: Use Of Optimal Oxygen and Getting Cpap Into The Delivery Roomentioning
confidence: 99%